White blood cell count and endothelin-1 vasoconstrictor tone in middle-aged and older adults - Kyle J. Diehl (Artery Research, 2012)
Background: Higher white blood cell (WBC) count is associated with impaired endothelium-dependent vasodilation. However, the influence of higher WBC count on endothelin (ET)-1 vasoconstrictor activity is currently unknown. We tested the hypothesis that adults with elevated WBC count demonstrate enhanced ET-1 system activity. Methods: Thirty-four healthy adults were studied: 17 with WBC count<5.0×109cells/L (lower WBC; 9M/8F; age: 53±2 yr) and 17 with WBC count>5.0×109cells/L (higher WBC; 10M/7F; 54±3 yr). Forearm blood flow (FBF) responses to intra-brachial infusion of ET-1 (5pmol/min for 20min) and selective ETA receptor blockade (BQ-123; 100nmol/min for 60min) were measured by venous occlusion plethysmography. Results: The vasoconstrictor response to ET-1 was significantly blunted (∼60%) in the higher WBC group versus the lower WBC group. The FBF responses to selective ETA receptor blockade were also significantly different (P<0.05) between the groups. In the lower WBC group, resting FBF increased marginally (∼5%) to BQ-123, whereas the increase in FBF to BQ-123 was significantly greater (∼15%) in higher WBC group. Furthermore, there was a significant relation between WBC count and FBF response to ET-1 (r=−0.43) and BQ-123 (r=0.41). Conclusions: Relative elevations in WBC count in middle-aged and older adults, independent of adiposity and other cardiometabolic risk factors, are associated with enhanced ET-1-mediated vasoconstrictor tone. Elevated ET-1 system activity may be a mechanism linking higher WBC count with increased cardiovascular risk.